Reducing Social Anxiety in Adolescents: The Efficacy of Group Counseling with Grounding Techniques - Aulia, Najwa; Rusman, Abdul Aziz (Journal of Social Work and Science Education, 2025)
This study examines the effectiveness of group counseling using grounding techniques in reducing social anxiety among seventh-grade students at State Junior High School 40 Medan, Indonesia. Social anxiety, characterized by an intense fear of social situations and concern over negative evaluation by others, has become increasingly common among adolescents, particularly in school environments. A total of 8 students identified as having moderate to high levels of social anxiety were selected through purposive sampling to participate in a four-session intervention program. Quantitative data were collected using a standardized social anxiety questionnaire administered before and after the intervention. Statistical analysis using the Wilcoxon Signed-Rank Test revealed a significant decrease in social anxiety levels following the intervention (p = 0.012), demonstrating the practical effectiveness of grounding strategies in alleviating symptoms of social discomfort and fear associated with peer interactions. These findings provide empirical support for integrating somatic and mindfulness-based techniques into school counseling services, especially for adolescents who are vulnerable to social anxiety. The study offers a promising direction for mental health practitioners and school counselors in developing non-pharmacological, easily applicable methods to support student well-being.